PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN: (Studi Kasus Pada Narassi Coffee Tasikmalaya) - Nurnawati, Rani; Muhammad Raihan (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to determine the effect of product quality and price on customer satisfaction at Narassi Coffee Tasikmalaya. The background of this study is based on the high competition of coffee shop businesses in Tasikmalaya City, so that the right strategy is needed to maintain and increase customer satisfaction. The method used is quantitative with a survey approach through a questionnaire distributed to 30 respondents. Data analysis was carried out using multiple linear regression. The results of the study indicate that product quality and price partially and simultaneously have a significant effect on customer satisfaction. The higher the consumer's perception of product quality and price, the higher the level of satisfaction felt. This finding implies that Narassi Coffee needs to continue to maintain product quality and set competitive prices in order to increase customer loyalty and satisfaction sustainably.